Challenges in representing the biaxial mechanical behavior of woven fabrics modeled by beam finite elements with contact. (1st February 2021) - Faccio Júnior, Celso Jaco; Gay Neto, Alfredo
Abstract: To establish a proper mechanical representation of woven fabric in the yarns-scale, one should take several decisions on model characteristics. A representative virtual specimen size has to be chosen, thus containing a desired yarns pattern, their in-plane-spacing and out-of-plane-spacing, crimp, bending stiffness, and a contact model to represent the interaction between yarns. Aiming at investigating the influence of such parameters on the overall mechanical behavior of a specimen of woven fabric material, the present work proposes a strategy for its modeling. The yarns are represented by geometrically exact beams and a master-master contact approach is employed to properly address their interaction between yarns. With numerical biaxial simulations, then, one may evaluate tests to obtain overall mechanical characteristics. For that, the proposed methodology is applied to a plain-weave glass fabric parametric study, a twill carbon fabric, and an imbalanced plain-weave. The aim is not only to address those specific textiles, but to provide an overall understanding of the relation between some modeling parameters and the expected mechanical response. The main contribution of the present work is the fabric modeling technique and the in-depth discussion of each modeling parameter involved which may be useful for novel designs.